Teachers researching their own practices in a process of curriculum change - Ponte, João Pedro da (2011)
This paper presents a practice-based teacher education task and reflects on using with a group of experienced teachers. I begin sketching a rationale for using such tasks, then I present the context of this activity and conclude referring the value of this approach for in-service and pre-service teacher education.